USE OF IT TECHNOLOGIES IN THE EDUCATION AND STUDY PROCESS AS A QUESTIONNAIRE RESEARCH METHOD (Scientific journal of the Fergana State University, 2024)
In order to study the attitude of the respondents to the use of information technologies in the educational process and sports training, a survey was conducted on the topic "use of IT technologies in the educational and educational process". During the survey, many respondents of UZGUFKS University were asked about the benefits of IT technologies for educational and training processes, as well as possible difficulties associated with their use and showed their views and opinions about the problems. According to the results of the survey, the use of information technologies is a relevant and important direction for improving the effectiveness of teaching and learning, but for the successful introduction of IT technologies, the training of teachers, the use of technical tools and educational materials came to the conclusion that a number of problems in the field of development should be solved.